Infant Mortality among African American Women Compared to European American Women in New York City - Taylor, Marian (ProQuest Dissertations & Theses, 2017)
The birth of low weight babies in the United States has not had a meaningful decline for the last 10 years.It continues to be a major predictor of fetal-infant mortality. In addition, the rate of low birth weight infants among African American women continues to be twice that of European American women. Low birth weight babies may experience breathing problems, vision problems, diabetes, hypertension, and cerebral palsy. The purpose of this study was to examine why the high infant mortality rate persist among the African American communities of Southeast Queens, New York City as compared to European American communities in the Borough of Queens, New York City.This was a quantitative retrospective study with a correlational design that utilized secondary data derived from vital records maintained by the New York City Department of Health and Mental Hygiene. The investigation was guided by the ecological model as the theoretical framework to collect, assess, and analyze the data. Logistic regression was used to predict the association of risk factors to infant mortality. Low birth weight, preterm birth, late or no prenatal care, and smoking during pregnancy were risk factors associated with a high mortality rate among African American women. Positive social change implications for this study include the development of a social intervention that will be culturally based for the diverse communities of Southeast Queens, New York City. There will be a collaborative effort in implementing the evidence-based interventions involving interested stakeholders.